Chromatographic retention indices in identification of chemical compounds - Babushok, V. I.
A brief overview of application of gas chromatographic retention indices (RIs)in the identification of chemical compounds is presented. Recent advances in the development of RI databases and the accumulation of experimental retention measurements in the form of computerized libraries are essential to increasing the efficiency of the identification process with the application of retention data. Currently available libraries of retention data provide the means for the more accurate identification of isomers, which have very similar mass spectra. The use of retention data allows filtering of MS hits, substantially decreasing the number of possible candidates. The application of the calibration function in combination with RI libraries simplifies the identification process. Multimode distributions of replicate measurements of RIs are often the result of isomer misidentification. Practical identification of isomers with close retention times relies strongly on elution-order information.
Keywords: CHEMICAL COMPOUND; DATA FILTERING; FALSE-POSITIVE IDENTIFICATION; GAS CHROMATOGRAPHY; HIT LIST; IDENTIFICATION; KOVÁTS INDEX; LINEAR INDEX; MASS SPECTROMETRY; RETENTION INDEX